Qualitative analysis of national documents on health care services and pharmaceuticals` purchasing challenges: evidence from Iran - Peivand Bastani; Mahnaz Samadbeik; Rassoul Dinarvand; Sara Kashefian-Naeeini; Soudabeh Vatankhah (BMC, 2018)
Abstract Background Iranian health sector encountered many challenges in resource allocation and health service purchasing during the past decades, the aim of this study was to determine the main challenges of the present process of health service purchasing for national policymakers and other developing countries with the same setting. Methods It was a qualitative study carried out via the complete content analysis of all relevant national documents from 2007 to 2014. In order to retrieve the related documents, we searched the official websites related to the Ministry of Health and Medical Education, four main Iranian insurance organizations, the Health Committee of the Parliament Profile, strategic vice president's site and Supreme Insurance Council. After recognition of documents, their credibility and authenticity were evaluated in terms of their publication or adjustment. For the analysis of documents, the four step-Scott method was used applying MAXQDA version 10. Results Findings illustrated that health service purchase challenges in the country can be classified in 6 main themes of policy-making, executive, intersectional, natural, legal and informational challenges with 26 subthemes. Furthermore, 5 themes of Basic Benefit Package, Reimbursement,Decision making, Technology and Contract are considered as the main Challenges in pharmaceutical purchasing area containing 13 relevant subthemes. Conclusions It seems that according to documents, Iran has faced many structural and procedural problems with the purchase of the best health interventions. So it is highly recommended to consider consequences derived from the present challenges and try to use these evidences in their policy making process to decrease the existed problems and move to better procurement of health interventions.